PANEL RESPONSE: FISCAL POLICY - What to do about the Surplus? - McHale, John (The Economic and Social Review, 2025)
It is a privilege to be part of the panel honouring Patrick Honohan’s contributions to Irish fiscal policy. Through his work as an academic, policy advisor and policymaker, Patrick has undoubtedly been one of the most practically influential economists – indeed perhaps the most influential – in the history of Irish economics. The word that most comes to mind in thinking of these contributions is wisdom. Ireland has been fortunate that this wise economist played such a central role during not one but two fiscal crises, first as advisor to the Taoiseach during the crisis of the 1980s and then as Governor of the Central Bank during the more recent sovereign debt crisis. Hopefully as a complement to the more micro-focused analyses of the other papers on this panel, not least Bara Rowntree’s excellent lead paper, I will take a macro perspective on fiscal policy, and in particular address the very live question about the appropriateness of current fiscal policy. Although the stakes are not as high as they were in the crisis management situations Patrick faced, fiscal policymaking today faces the difficult challenge of balancing counter cyclical, sustainability and risk management concerns at a time where there is also strong pressure to use the surplus to meet real societal needs. Hopefully that balancing can be done in a way that ensures that future advisors and policymakers do not have confront new crises in the years ahead.